Ehrlich's Geomicrobiology - Ehrlich, Henry Lutz;Ed. Newman, Dianne K;Ed (CRC Press, Taylor & Francis Group, 2016)
"Advances in geomicrobiology have progressed at an accelerated pace in recent years. Ehrlich’s Geomicrobiology, Sixth Edition surveys various aspects of the field, including the microbial role in elemental cycling and in the formation and degradation of minerals and fossil fuels. Unlike the fifth edition, the sixth includes many expert contributors besides the editors, providing added depth to each topic and broadening this edition’s overall insight into geomicrobiology."-